(untitled) (The São Paulo Journal of Mathematical Sciences, 2010)
Corepresentations of some one parametric equipped posets over an arbitrary quadratic field extension F c G are studied and classified. Complete matrix canonical forms of indecomposable corepresentations of several sincere one parametric equipped posets are presented, including those for two critical equipped posets. Some important properties of corepresentations of equipped posets are established.